Memories and studies - James, William, 1842-1910 (The Floating Press, 2012)
William James was a towering intellectual figure with a vast knowledge base that transcended typical disciplinary boundaries. In this collection of essays, William James explores the topics of memory and cognition through the lenses of philosophy, psychology, and his own personal life experiences, all recounted in his uniquely engaging writing style.